Dielectric permittivity of semiconductors with narrow forbidden gap in the long-wave limit - Sheka, D.; Korol, Anatoliy; Шека, Д. І.; Король, Анатолій Миколайович (My University, 1976)
In the random phase approximation the dielectric permittivity is evaluated for a semiconductor with a band structure described by Kane’s energy band scheme. It is demonstrated that the fact that several hole bands have been taken into account, when the operator of the kinetic energy ceased to be the Dirac one plays the principal role in the calculation of the static dielectric permittivity ε(q →0).
Keywords: narrowgapped semiconductors; dielectric permittivity; longwave limit; вузькозонні напівпровідники; діелектрична проникність; довгохвильова межа; узкозонные полупроводники; диэлектрическая проницаемость; длинноволновой предел; кафедра фізики та професійної безпеки